Dukungan Informasional terhadap Keberfungsian Sosial pada Generasi Sandwich oleh Komunitas Online @Sobatsandwich - Nurul Aisyah; Irhamni Rahman (Lembaga Pengembangan Kinerja Dosen, 2024)
The sandwich generation, a group of people who are caught between their parents and children whom they are responsible for, experience a significant physical and mental burden. Considering the challenges they face, information support from @SobatSandwich as an online community can be a way to enhance their social functioning. This study focuses on the information received by the sandwich generation from the Sobat Sandwich account because the sandwich generation is surrounded by a burden of responsibility. The purpose of this research is to examine the influence of informational support toward sandwich generation social functioning by the online community @sobatsandwich. This study use a quantitative approach with surveys using questionnaires, and it shows that 77% of respondents feel that the informational support provided by the @SobatSandwich account helps them to obtain information about the sandwich generation and assists them in setting future goals which shows that the informational support has an impact on the social functioning of the sandwich generation.